Motivasi kerja dan etos kerja islam terhadap kinerja karyawan dengan mediasi disiplin kerja: Studi pada PT Astra International Tbk Cabang Ungaran - Kaironi, Kaironi; Fitriyani, Endah Nur (Nur Science Institute, 2023)
This study aims to analyze the influence of Islamic work motivation and work ethic on employee performance, with work discipline as a mediating variable. This study uses a quantitative method with a population employed by PT Astra International Ungaran Branch. The sampling technique was purposive sampling, with 34 respondents. Data analysis used path analysis techniques. The results of the study indicate that Islamic work motivation and work ethic have a positive effect on work discipline. However, Islamic work motivation and work ethic do not affect employee performance. On the contrary, work discipline has a positive effect on employee performance. Another result is that work discipline was able to mediate the influence of Islamic work motivation and work ethic on employee performance.